2021
DOI: 10.1590/1980-265x-tce-2020-0380
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Symptoms of Depression Among Older Adults During the Covid-19 Pandemic

Abstract: Objective: to identify factors associated with depressive symptoms among older adults during the COVID-19 pandemic. Method: a cross-sectional study developed in all regions of Brazil, using an electronic form among older adults aged 60 or over. Data were collected from April 17 to May 15, 2020. Measures of central tendency and dispersion were used. For comparison of means, Student’s t-test and analysis of variance were applied, considering p≤0.05. For association of factors, chi-square was adopted with bivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
4
8
0
15
Order By: Relevance
“…The data showed a greater number of women, with a partner and higher education. Similar results were identified in national 16 and international 17,18 research. In addition, it was identified that 39.7% of the participants had depressive symptoms, similar results were found in a Chinese study (30.8%) 16 in Bangladesh 17 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The data showed a greater number of women, with a partner and higher education. Similar results were identified in national 16 and international 17,18 research. In addition, it was identified that 39.7% of the participants had depressive symptoms, similar results were found in a Chinese study (30.8%) 16 in Bangladesh 17 .…”
Section: Discussionsupporting
confidence: 89%
“…In relation to marital status, older people with partners had a lower score of depressive symptoms. Similar results were identified in a population-based study carried out in southern Brazil, in which the factors associated with the occurrence of depression among older people were being female, being separated and being widowed during the pandemic 16 . However, this association, before the pandemic, was already a concern, as identified in the study carried out with 388 older people in Mato Grosso 19 .…”
Section: Discussionsupporting
confidence: 86%
“…Corroborando os autores, um estudo identificou que os principais fatores associados aos sintomas de depressão entre pessoas idosas durante a pandemia da COVID-19 foram o sexo feminino, a baixa condição socioeconômica e a baixa escolaridade. Além disso, pessoas idosas que possuíam ocupações que os expunham diretamente à COVID-19 apresentaram maiores escores de depressão (18) .…”
Section: Discussionunclassified
“…Os dados demostraram maior número de mulheres, com companheiro e estudo superior. Resultados similares foram identificados em pesquisas nacionais 16 e internacionais 17,18 . Ademais, se identificou que 39,7% dos participantes apresentavam sintomas depressivos, similares resultados foram encontrados em estudo (30,8%) 16 e em Bangladesh (40,1%) 17 .…”
Section: Discussionunclassified
“…Em relação ao estado civil, os idosos com companheiros apresentaram menor escore de sintomas depressivos. Resultados similares foram identificados no estudo de base populacional realizado no Sul do Brasil, em que os fatores associados à ocorrência de depressão entre os idosos foram ser do sexo feminino, ser separados e viúvos durante a pandemia 16 . Contudo, essa associação, antes da pandemia, já era uma preocupação, como identificado no estudo realizado com 388 idosos em Mato Grosso 19 .…”
Section: Discussionunclassified